2017
DOI: 10.21037/jtd.2017.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human brain natriuretic peptide on the prognosis of patients with acute anterior myocardial infarction undergoing primary percutaneous coronary intervention: a prospective, multi-center, randomized clinical trial

Abstract: Background: This study aims to investigate the effects of recombinant human brain natriuretic peptide (rhBNP) on serum enzyme data, cardiac function parameters and cardiovascular events in patients with acute anterior myocardial infarction (MI). Methods: A total of 421 patients with acute anterior or extensive anterior MI were collected from 20 hospitals. These patients were randomly divided into two groups: rhBNP and control groups. Both groups of patients received primary percutaneous coronary intervention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In addition to expanding the coronary and lung circulation, BNP reduces myocardial oxygen consumption and increases coronary blood flow, which prevents cardiac remodeling (34,35). The present study revealed that the serum levels of troponin I and NT-proBNP were significantly decreased in the GFR >53 group at final follow-up.…”
Section: Discussionsupporting
confidence: 47%
“…In addition to expanding the coronary and lung circulation, BNP reduces myocardial oxygen consumption and increases coronary blood flow, which prevents cardiac remodeling (34,35). The present study revealed that the serum levels of troponin I and NT-proBNP were significantly decreased in the GFR >53 group at final follow-up.…”
Section: Discussionsupporting
confidence: 47%
“…The therapeutic effect of rhBNP in the clinical management of cardiac diseases is well recognized [23]. BNP is a natural factor against cardiac remodeling, and selectively expands coronary and lung circulation, increases coronary blood ow and reduces the consumption of myocardial oxygen [24,25]. Our results revealed that rhBNP signi cantly decreased the serum concentrations of TnI and NT-proBNP in follow-up.…”
Section: Discussionmentioning
confidence: 57%
“…The related data show that the blood flow of the bridge is positively correlated with the diameter of the distal coronary artery. When there is stenosis or obstruction of the distal vessel, the anastomotic site is not unobstructed and the blood flow is small 14 . The positive correlation between the diameter of the distal target vessel > 1.5mm and the increase of CK-MB may be due to the decrease of blood flow caused by a large vascular plaque load, which in turn affects the increase of CK-MB level 15 each of whom presented with a normal ECG and was subjected to emergency coronary angiography (CAG).…”
Section: Discussionmentioning
confidence: 99%